Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have here a complex equation:

$\cos(iz)=\sin(iz),\ \ \ \ z\in C$

How do we get the solutions of this equation? I started replacing $z=x+iy$ but I can't continue. Any suggestions please?

Thank you very much

share|cite|improve this question
are you familiar with hyperbolic functions? – user31280 Nov 5 '12 at 13:28
up vote 2 down vote accepted

So, $\tan(iz)=1$

So, $iz=m\pi+\frac\pi 4$ where $m$ is any integer.

$z=\frac 1 i(m\pi+\frac\pi 4)=-i\frac{(4m+1)\pi }4$

Now, the difference of two consecutive values of $iz$ is $-i\frac{\{4(r)+1\}\pi }4-\left(-i\frac{\{4(r+1)+1\}\pi }4\right)=\pi i$

As we know $e^{2\pi i}=1$ and $$\tan(iz)=1\iff \frac{e^z+e^{-z}}{e^z-e^{-z}}=i\iff e^{2z}=-i$$ there will be $\frac{2\pi}\pi=2$ distinct solutions(Compare the result with that of the next method).

Using Euler's identity and Euler's formula,

$$\cos (iz)=\frac{e^{i(iz)}+e^{-i(iz)}}2=\frac{e^z+e^{-z}}2$$

$$\sin (iz)=\frac{e^{i(iz)}-e^{-i(iz)}}{2i}=i\frac{e^z-e^{-z}}2$$

So, $$\frac{e^z+e^{-z}}2=i\frac{e^z-e^{-z}}2$$

or, $$e^{2z}+1=i(e^{2z}-1)\implies e^{2z}=-i=e^{-\frac{i\pi}2}$$ for $-i=R(\cos A+i\sin A)\implies R=\sqrt{0^2+(-1)^2}=1$ and $\cos A=0,\sin A =-1\implies A=-\frac{i\pi}2$

So, $$ e^{2z}=e^{2n\pi i-\frac{i\pi}2}$$ where $n$ is any integer as $e^{2n\pi i}=\cos(2n\pi)+i(\sin2n\pi)=1$.

So, $z=\frac 12 (2n\pi i-\frac{i\pi}2)=i\frac\pi 4(4n-1)$ where $0\le n<2$ or more generally any two in-congruent values of $n\pmod 2$ will give us the 2 distinct solution of $e^{2z}=-i$ and consequently, of the given equation.

share|cite|improve this answer
@Mark, I've added a relatively simpler solution which I thought of on my way home. One may try to resemblance with doraemonpaul's answer. – lab bhattacharjee Nov 5 '12 at 15:57

I think you treat this question too complicated.

Let $x=iz$ ,

Then $\cos x=\sin x$

$\cos x=\cos\left(\dfrac{\pi}{2}-x\right)$

$x=2n\pi+\dfrac{\pi}{2}-x$ , $\forall n\in\mathbb{Z}$

$2x=\dfrac{(4n+1)\pi}{2}$ , $\forall n\in\mathbb{Z}$

$x=\dfrac{(4n+1)\pi}{4}$ , $\forall n\in\mathbb{Z}$

$iz=\dfrac{(4n+1)\pi}{4}$ , $\forall n\in\mathbb{Z}$

$z=-\dfrac{(4n+1)\pi i}{4}$ , $\forall n\in\mathbb{Z}$

share|cite|improve this answer

What if you write $\cos(z)=\frac 12 (e^{iz}+e^{-iz})$ and $\sin(z)=\frac 1{2i}(e^{iz}-e^{-iz})$?

share|cite|improve this answer

Putting, as you did, $\,z=x+iy\,$ , but only in a later step, we get:

$$\frac{e^{-z}+e^z}{2}=:\cos iz=\sin iz:=\frac{e^{-z}-e^z}{2i}\Longrightarrow$$

$$ie^{-z}+ie^z=e^{-z}-e^z\Longrightarrow i(1+e^{2z})=1-e^{2z}\Longrightarrow$$

$$i[1+e^{2x}(\cos 2y+i\sin 2y)]=1-e^{2x}[\cos 2y+i\sin 2y)]\Longrightarrow$$

$$\left(-e^{2x}\sin 2y\right)+i[1+e^{2x}\cos 2y]=\left(1-e^{2x}\cos 2y\right)-ie^{2x}\sin 2y$$

Comparing real and imaginary parts:

$$-e^{2x}\sin 2y=1-e^{2x}\cos 2y$$

$$1+e^{2x}\cos 2y=-e^{2x}\sin 2y$$

Can you take it from here?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.